Objective Review on Commercially Viable Prelithiation Techniques for Lithium‐ion Batteries - Victor Lau Jr; Chih‐ying Kuo; Prof. Chung‐wen Lan (ChemElectroChem, 2024)
Abstract The rapid increase in global energy storage demands has necessitated the adoption of next‐generation lithium‐ion battery anode materials. However, these anode materials′ high lithium loss and poor cycling stability hinder their commercial application. The emergence of prelithiation offers a promising strategy for improving the lithium utilization efficiency of these active materials, thereby providing a solution for the performance bottleneck of next‐generation anode materials. The current review compiled and systematically discusses recent and notable prelithiation techniques concerning its potential for commercialization. The challenges currently hindering easy commercial adoption of the various prelithiation techniques and the potential development direction of each technique are analyzed. The commercial potential of the prelithiation methods is discussed based on the following four main criteria: electrochemical performance, ambient stability, cost, and industrial scalability. Finally, insights regarding further development of each prelithiation technique are provided, considering their unique advantages and disadvantages. The current review allows the industry and researchers to compare the commercial potential of various prelithiation techniques while considering their specific circumstances.